Factors determining students’ learning creativity in SMPN 9 Surakarta - Ayu Nabila Akifah Noor (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2017)
The research aims at finding out the determinant factors of: 1) students’ learning creativity; 2) school quality; 3) students’ personality; 4) the correlation between school quality with the students’ learning creativity; 5) the correlation between students’ personality with students’ learning creativity; and 6) the correlation between school qualities with students’ personality. The data used data were derived from VIII students of SMP Negeri 9 Surakarta. The sample was 161 students out of 277 students of the population. The sample were from 9 classes and determined by proporsional random sampling technique. The data gathered thorugh questionnaire, measuring  the students’ learning creativity, the school quality, and the students’ personality. The analysis employed LISREL PROGRAM of 8.54 version.The results of the research showed that:1) there were five determinant factors of learning creativity, namely sensitivity toward problem, the fluency in producing a new idea, the flexibelity in expressing solution, the originality in formulating the idea, and the detail in analyzing the idea; 2) there were seven determinant factors of school quality, namely teacher quality, teaching quality, quality of administration services, students’ commitments, parents support, resources accessibility, and learning comfort; 3) there were eight determinant factors of students’ personality, namely self confident, initiative, competitive, adaptive, responsive, challenge lover, risk taker, and persistency; 4) there was a positive and significant correlation between school quality and students’ personality; 5) there was positive but not significant correlation between school quality and students’ learning creativity; and 6) there was positive and not significant correlation between students’ personality and students’ learning creativity. Keywords: determinant factors, learning creativity, junior high school AbstrakPenelitian ini bertujuan untuk menemukan faktor penentu:1) kreativitas belajar siswa; 2) kualitas sekolah; 3) personalitas siswa; 3) hubungan kualitas sekolah dengan kreativitas belajar; 4) hubungan personalitas dengan kreativitas belajar; (5) hubungan kualitas sekolah dengan personalitas.Data bersumber dari siswa kelas VIII SMP Negeri 9 di Surakarta. Populasi penelitian adalah siswa kelas VIII berjumlah 277 siswa. Penentuan ukuran sampel menggunakan Tabel Isaac- Michael sejumlah 161 siswa yang terbagi dalam 9 kelas. Pengambilan sampel menggunakanproportional random sampling. Teknik pengumpulan data menggunakan angket dengan mengukur indikator dari 3 variabel yakni kreativitas belajar, kualitas sekolah, dan personalitas. Analisis data menggunakan Program LISREL Versi 8.54. Hasil penelitian menunjukkan bahwa: 1) lima faktor penentu kreativitas belajar yakni sensitivitas terhadap masalah, kelancaran menghasilkan gagasan baru, keluwesan mengungkapkan solusi, keaslian merumuskan gagasan, dan kerincian menguraikan gagasan; 2) ada tujuh faktor penentu kualitas sekolah yakni kualitas guru, kualitas pengajaran, kualitas pelayanan administrasi, komitmen siswa, dukungan orangtua, aksesibilitas sumber, dan kenyamanan belajar; 3) ada delapan faktor penentu personalitas siswa yakni percaya diri, memiliki inisiatif, kompetitif, adaptif, responsif, menyukai tantangan baru, senang menghadapi risiko, dan memiliki daya bangkit; 4) ada hubungan yang positif dan signifikan antara kualitas sekolah dengan personalitas siswa; 5) ada hubungan yang positif dan tidak signifikan antara kualitas sekolah dengan kreativitas belajar siswa; 6) ada hubungan positif dan tidak signifikan antara personalitas dan kreativitas belajar siswa.  Kata kunci: faktor penentu, kreativitas belajar, sekolah menengah pertama